Availability of Essential Antidotes and the Role of Community Pharmacists in the Management of Acute Poisoning: A Cross-Sectional Study in Ethiopia - Zemene Demelash Kifle MSc; Dawit Kumilachew Yimenu; Chilot Abiyu Demeke; Asmamaw Emagn Kasahun; Ebrahim Abdela Siraj; Adane Yehualaw Wendalem; Zegaye Agmassie Bazezew; Abebe Basazn Mekuria (SAGE Publishing, 2022)
Background Morbidity and mortality related to acute poisoning is a major public health issue in both developing and developed countries. Community pharmacists have a crucial role in ensuring drug availability, increasing drug safety, counseling patients, overdose risk reduction and management, and provision of appropriate drug information. This study aimed to assess the availability of necessary antidotes in community pharmacies in Gondar and Bahir-Dar cities, Ethiopia, and the role of community pharmacists in the management of acute poisoning. Methods A cross-sectional survey was conducted in Gondar and Bahir-Dar cities. A self-administered, structured questionnaire was used for data collection and Statistical Package for Social Sciences (SPSS) version 24.0 was used for data analysis. Chi-square analysis was computed to identify the associated factors with a confidence interval of 95% and a P value less than .05 was used as a cut-point for statistical significance. Results Out of 101 community pharmacies invited to participate in the study, 80 of them completed the survey with a response rate of 79.2%. The overall mean antidote availability score was .59 (SD = .837), which falls within the definition of Poor availability. None of the pharmacies had kept all of the antidotes, and the maximum number of an antidote kept by a single pharmacy was 7 out of nineteen essential antidotes surveyed. The most commonly reported reason for the unavailability of essential antidotes was stock was not ordered (56.3%) followed by stock ordered but not delivered from suppliers (wholesalers) (20.0%). More than 3 fourth of the respondents (83.8%) had poor knowledge about the antidotes for the common poisonings. Conclusion There was a significantly very low availability of essential antidotes in the community pharmacies. Strategies should be implemented to improve pharmacist's knowledge about antidotes, and management of poisoning emergencies through on-job training and provision of reference materials.